Flow cytometry assay to evaluate lipid production by the marine microalga Tetraselmis sp. using a two stage process. (November 2021) - Dammak, Mouna; Ben Hlima, Hajer; Elleuch, Fatma; Pichon, Chantal; Michaud, Philippe; Fendri, Imen; Abdelkafi, Slim
Abstract: Tetraselmis sp. strain MD-01, a microalga isolated from the Tunisian marine coast, has been studied for autotrophic lipids production with two stage process. This strategy was conducted for maximum cells production under moderated conditions (2.12 g L −1 ), followed by cultivation under stressed conditions to induce lipid synthesis. High irradiance (300 μmol m −2 s −1 ) and nitrogen depletion (S mode) showed better carotenoids accumulation and lower chlorophylls content in microalgae compared to those obtained in biomass cultivated under high irradiance (Sg mode). This two-stage strategy allowed to increase of lipid content in cells cultivated in Sg and S modes from 18% DW (stage I) to 50 and 61.5% DW (stage II), respectively, with an increase of saturated and long chain fatty acids levels. Based on fluorometry analyses, an increase of lipids in Nile-Red stained cells and a decrease of chlorophylls auto-fluorescence under stressed conditions were shown. From spectral data, the lipids: amide I ratio obtained from S mode was 2.17 and 4.45 times higher than that from Sg mode and control conditions, respectively. These results revealed the potential of Tetraselmis strain MD-01 for biodiesel production. Graphical abstract: Image 1